THE RELATIONSHIP BETWEEN ENGAGEMENT AND ACADEMIC BURNOUT - Marius Costel ESI; Narcisa Loredana POSTEUCĂ EȘI (Association of Social and Educational Innovation, 2023)
The involvement of students in the quality of the act of learning reveals the very idea of their active participation in such an educational approach. This assumption requires the consideration of a process of continuous training, but also of sustainable development of what the quality of the training/learning process stands for. Such a process requires a clear awareness of what constitutes the way of organizing personal and professional resources as they are found in students' lives. The quality of the activities carried out in the student environment largely depends on how they organize their relationship between resources and performance. Realizing one's own potential is most often achieved by taking into account the ability to relate to the idea of success, but also to emotional and sometimes even to physical stress. Hence the validated/confirmed studies of some specialists on aspects relating to possible correlations among anxiety, self-esteem, desirable or less desirable behaviors, fatigue, stress, performance and so on. The relevance of this type of study is supported by the degree of novelty and topicality of the subject, in the context of the advance of research in the psycho-pedagogical and educational field. Also, the scientific importance of this approach is justified by the need to calibrate educational policies according to the student's psycho-emotional resources. The analysis carried out can also be useful as a research base for further developments intended to provide solutions to improve the phenomenon of the academic burnout.